Outcome and Management of Sepsis at RozhHalat Emergency Hospital in Erbil –Kurdistan region of Iraq - Qader Ahmad, Samir; Muhamad Ismaeel, Shakawan; Ahmed Mohammed, Dara Ahmed Mohammed; Fathulla Ahmed, Halgurd (Kurdistan Journal of Applied Research, 2018)
Sepsis is a very common condition in emergency hospitals and presentation is variable, it is under diagnosed with very high mortality rate. All patients with infection are at risk of developing sepsis. Sepsis is a complex condition characterized by activation of inflammatory process and coagulation system in response to microbial insult. An observational prospective study was carried out at RozhHalat emergency hospital in Erbil-Kurdistan region of Iraq between February 2017 to January 2018.The study was approved by the scientific and ethical committee of Kurdistan board of medical specialties. 50 patients aged between (10 - 80) years old presented to this hospital with sign and symptoms of infection were recruited to this study. 50 patients with signs and symptoms of sepsis were recorded in this study. The mean age was 47 with male to female ration of 2:3 (42% male and 58% female). The overall mortality rate was high at 68% with higher rate among female and older age group. The blood culture was positive in 74% of cases of which 52% were gram positive and 22% were gram-negative microorganisms. A Positive blood culture associated with higher mortality rate of 81% compared with 21% if the blood culture was negative. In majority of cases the site of infection was from multiple source (34%) followed by respiratory infection (26%).Skin and soft tissue infection was associated with the lowest mortality of 2.9%. High number of cases (82%) developed complications and 52% of cases developed more than 2 organ failures. All patients received empirical antibiotic therapy however 46% of cases received the wrong antimicrobials. The survival rate was higher (44%) among patients given the right antibiotics. Similarly patients had better chance of survival if appropriate fluid resuscitation therapy was give. The overall mortality among vasopressor treated patients were 72% compared with 78% chance of mortality if they were not treated with any vasopressor therapy, among those who received inotropic support Noradrenaline associated with higher survival rate(72%). A qSOFA score of more than 2 associated with 86.4 % of mortality compared with 75.5% mortality with similar SIRS criteria. Factors associated with high mortality were: female gender, older age group, positive blood culture, wrong antibiotics therapy, less fluid resuscitation, multisource of infection, multi-organ failure, high lactic acid level and high qSOFA score. This study shows that sepsis is associated with high overall mortality rate of 68% in the RozhHalat emergency hospital and higher rate of death among female and older age group. Negative blood culture, appropriate use of antibiotics and fluid therapy associated with better chance of survival. Vasopressor therapy did not result in better survival outcome except for Noradrenaline. The qSOFA score is as good as SIRS criteria in predicting mortality. High lactate, multi-organ failure and multisource of infection associated with the worst outcome.